Comparative effectiveness of various teaching modes, including PBL, CBL, and CTTM in paediatric medical education with combined online and offline approaches - Yun Shang; Kun-Feng Cao; Jun-Yan Yue; Shu-Zhen Zhao; Shang-Hui Hao; Ya-Zhou Sun; Qing-Yang Cui; Hui-Min Guo; Cheng-He Tang (BMC Medical Education)
Abstract Objective To explore the differences in the effectiveness of various teaching methods combining online and offline modes in paediatric medical education. Methods Fourth-year medical paediatric students at our university in 2020 were randomly divided into three groups: a control group, experimental group 1, and experimental group 2, with 30 students in each group. The control group received traditional teaching, experimental group 1 received a combination of online and offline teaching using two methods simultaneously, and experimental group 2, in addition to the methods used in experimental group 1, engaged in real-case teaching in the ward. The teaching outcomes were evaluated through theoretical exams, clinical skills assessments, and questionnaires. Results Experimental groups 1 and 2 were superior to the control group concerning theoretical examination and overall scores (P < 0.05). Experimental group 2 was superior to experimental group 1 and the control group in clinical skills examination scores (P < 0.05). The satisfaction rate for the questionnaire was highest in experimental group 2 (P < 0.05). Conclusion The combined use of various teaching methods with online and offline modes is more effective than using traditional teaching methods only in paediatric education. It enhances the overall competence of paediatric students, especially in terms of improving clinical skills, and is well-received by both students and teachers.